Corporate spin-offs value creation : parent & spin-off view - Vilppula, Joona (2015)
Corporate spin-offs have gained popularity over the past few years. Despite of this in Finnish media and university teaching this phenomenon has gained little attention. This study aims to fulfill this knowledge gap. Spin-off is a restructuring procedure where company splits into two separate legal entities via pro-rata transaction basis. I researched this phenomenon by event-study methodology which has been quite popular also in earlier studies. I have com-pared parent and spin-off stock performance in order to reveal potential value gains for investors. Parent company is analyzed also from the announcement period where we find strong positive abnormal returns associated with announcement of spin-offs. However by comparing spin-off execution period abnormal returns I find that spin-offs performed worse than their former parents. I find no evidence that in short term spin-offs were valued more than their former parents by investors.